The Impact of Arm Muscle Explosive Strength and Hand-Eye Coordination on Smash Performance Among Players at the Tulung Selapan Badminton Union Club - Antoni, Antoni; Lanos, Muhsana El Cintami; Rizhardi, Rury (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to evaluate the impact of arm muscle explosive strength and hand-eye coordination on smash performance among players at the Tulung Selapan Badminton Union Club. The research employs a quantitative method with a correlational approach. The study population and sample consist of 20 participants from the Tulung Selapan Badminton Union Club. Data collection was carried out using tests, and data analysis was performed through simple and multiple regression tests using the F-test formula. The findings of this study are 1) Arm muscle explosive strength has a significant impact on smash performance; 2) Hand-eye coordination also significantly affects smash performance; 3) Both arm muscle explosive strength and hand-eye coordination together have a significant impact on smash performance.